Modellierung und Numerische Simulation des Schichtaufbaus bei einem PUR-Sprühverfahren - Xinyi Gu (2011)
The material, polyurethane (PUR), has been used in spray process for years. It is sprayed into a mould or a substrate with mixed long fibers to obtain a composite material. In the research project SFPURC (Spray-simulation Fiber PUR-Composites), a new simulation model for the spray-process technique is developed and applied, in order to estimate and optimize the corresponding distributions of PUR and fibers within a substrate. In this study, a simulation model was established to estimate the layer structure during the PUR-spray process without the presence of fibers. Thus, the trajectory of PURparticles together with their inter-collision and their final distribution on the substrate were simulated using different approaches and compared with experimental results.